From Web2 to Web3: Strategic Transformation of Digital Marketing Using Blockchain Technology - Yunus, Fuwad; Shahid, Sanya; Sattar, Abdul (Inverge Journal of Social Sciences, 2026)
This study aimed to examine the role of blockchain technology in transforming digital marketing within the emerging Web3 environment, with a specific focus on its impact on consumer trust and marketing efficiency. The research primarily investigated the relationship between blockchain technology as the independent variable and digital marketing transformation as the dependent variable, while also considering consumer trust and marketing efficiency as key outcome variables. A quantitative research design was adopted, and data were collected from 250 respondents, including digital platform users and marketing professionals, using a structured questionnaire based on a 5-point Likert scale. Statistical analyses, including reliability, correlation, and regression, were conducted to test the proposed hypotheses and evaluate the relationships among variables. The findings revealed that blockchain technology had a significant positive impact on digital marketing transformation (β = 0.68, p < 0.001) and consumer trust (β = 0.72, p < 0.001). Digital marketing transformation significantly influenced marketing efficiency (β = 0.70, p < 0.001). The results also indicated that consumer trust played a mediating role in enhancing marketing efficiency, highlighting the importance of transparency and data security in digital environments. The study provides practical implications for organizations by emphasizing the adoption of blockchain-based marketing systems to improve transparency, reduce operational inefficiencies, and strengthen consumer trust. It also highlights the strategic importance of decentralized platforms in shaping the future of digital marketing. References Basal, M., & Şarkbay, Ö. F. (2026). Web3-driven digital marketing and consumer protection. Frontiers in Blockchain. https://doi.org/10.3389/fbloc.2026.1726047 Beck, R., Müller-Bloch, C., & King, J. L. (2018). Governance in the blockchain economy. Journal of the Association for Information Systems, 19(10), 1020–1034. https://doi.org/10.17705/1jais.00518 Bottoni, P., Gessa, N., Massa, G., Pareschi, R., Selim, H., & Arcuri, E. (2020). Intelligent smart contracts for innovative supply chain management. Frontiers in Blockchain, 3, 535787. https://doi.org/10.3389/fbloc.2020.535787 Casino, F., Dasaklis, T. K., & Patsakis, C. (2019). A systematic literature review of blockchain-based applications. Telecommunications Systems, 71(2), 183–210. https://doi.org/10.1007/s11235-018-0457-5 Chenn, A. (2024). Blockchain marketing analytics: A conceptual framework. SSRN Electronic Journal. https://doi.org/10.2139/ssrn.5239010 Frizzo-Barker, J., Chow-White, P. A., Adams, P. R., Mentanko, J., Ha, D., & Green, S. (2020). Blockchain as a disruptive technology for business. Journal of Business Research, 116, 297–307. https://doi.org/10.1016/j.jbusres.2020.05.014 Huang, R., Chen, J., Wang, Y., Bi, T., & Zheng, Z. (2023). An overview of Web3.0 technology: Infrastructure, applications, and popularity. IEEE Access. https://doi.org/10.1109/ACCESS.2023.3274512 Ilyas, D. (2024). Revolutionizing digital marketing with blockchain technology: An empirical investigation of Pakistani SMEs. IBT Journal of Business Studies, 20(1), 65–90. https://doi.org/10.46745/ilma.jbs.2024.20.01.03 Köppelmann, L., & Blask, T. B. (2024). Web3 marketing for enterprises: A systematic literature review. SSRN Electronic Journal. https://doi.org/10.2139/ssrn.4864000 Kshetri, N. (2018). Blockchain’s roles in strengthening cybersecurity. Telecommunications Policy, 42(4), 273–283. https://doi.org/10.1016/j.telpol.2017.09.003 Kumar, A., & Brar, V. (2024). Digital marketing and role of blockchain in digital marketing industry. International Journal of Advanced Research, 1(7), 383–387. https://doi.org/10.61359/11.2206-2438 López Rodríguez, A. M. (2025). Consumer protection in blockchain-based metaverses. Frontiers in Blockchain. https://doi.org/10.3389/fbloc.2025.1675735 Melnyk, A. (2024). Marketing evolution: From traditional to Web 3.0. DOAJ Journal, 10(5), 273–281. https://doi.org/10.30525/2256-0742/2024-10-5-273-281 Puthal, D., Malik, N., Mohanty, S. P., Kougianos, E., & Yang, C. (2018). The blockchain as a decentralized security framework. IEEE Consumer Electronics Magazine, 7(2), 18–21. https://doi.org/10.1109/MCE.2017.2776459 Rafiq-uz-Zaman, M. (2023). The impact of digital literacy on students’ learning outcomes: A comprehensive review. Inverge Journal of Social Sciences, 2(2), 194–205. https://doi.org/10.63544/ijss.v2i2.210 Rafiq-uz-Zaman, M. (2025). The integrated skill-based education framework (ISEF): An empirically grounded model for reforming skill-based education in Pakistan. Global Social Sciences Review, X(III), 157–167. https://doi.org/10.31703/gssr.2025(X-III).14 Rejeb, A., Rejeb, K., & Treiblmaier, H. (2020). Blockchain technology in marketing. Industrial Marketing Management, 90, 343–356. https://doi.org/10.1016/j.indmarman.2020.07.020 Saberi, S., Kouhizadeh, M., Sarkis, J., & Shen, L. (2019). Blockchain technology and its relationships to sustainable supply chain management. International Journal of Production Research, 57(7), 2117–2135. https://doi.org/10.1080/00207543.2018.1533261 Sanghvi, M., Ubarhande, P., Chandani, A., Pathak, M., Wagholikar, S., Bagade, S., & Atiq, R. (2026). Trends in blockchain in finance. Frontiers in Blockchain. https://doi.org/10.3389/fbloc.2026.1730387 Sharma, C. (2025). Mapping the evolution of digital marketing research. Information, 16(11), 942. https://doi.org/10.3390/info16110942 Stallone, V., Wetzels, M., & Klaas, M. (2021). Applications of blockchain technology in marketing. Blockchain Research and Applications, 2(3), 100023. https://doi.org/10.1016/j.bcra.2021.100023 Supraveen, U. J., Srivastava, D., Sharma, Y. K., Sharma, G., Kulkarni, N., & Joseph, C. (2025). Blockchain and marketing: Enhancing consumer trust and transparency. Economic Sciences Journal. https://doi.org/10.69889/wwv40184 Tan, T. M. (2024). A blockchain-based approach to marketing transformation. Journal of Business Research, 172, 114143. https://doi.org/10.1016/j.jbusres.2024.114143 Tapscott, D., & Tapscott, A. (2017). Blockchain revolution. MIT Sloan Management Review. https://doi.org/10.7551/mitpress/11481.001.0001 Thomason, J. (2026). Ethics and governance in Web3. Frontiers in Blockchain. https://doi.org/10.3389/fbloc.2026.1832534 Treiblmaier, H. (2019). Toward more rigorous blockchain research. Frontiers in Blockchain, 2, 3. https://doi.org/10.3389/fbloc.2019.00003 Wan, S., Lin, H., Gan, W., Chen, J., & Yu, P. S. (2023). Web3: The next internet revolution. IEEE Transactions. https://doi.org/10.1109/TNSE.2023.3261234 Xiangjuan, J. (2025). Integration and innovation of blockchain in Web3.0. World Wide Web. https://doi.org/10.1007/s11280-024-01319-7 Yli-Huumo, J., Ko, D., Choi, S., Park, S., & Smolander, K. (2016). Where is current research on blockchain technology? PLOS ONE, 11(10), e0163477. https://doi.org/10.1371/journal.pone.0163477